Assessing mNIS+7Ionis and international neurologists' proficiency in a familial amyloidotic polyneuropathy trial. Issue 5 (7th April 2017) - Dyck, Peter J.; Kincaid, John C.; Dyck, P. James B.; Chaudhry, Vinay; Goyal, Namita A.; Alves, Christina; Salhi, Hayet; Wiesman, Janice F.; Labeyrie, Celine; Robinson‐Papp, Jessica; Cardoso, Márcio; Laura, Matilde; et al.
ABSTRACT: Introduction: Polyneuropathy signs (Neuropathy Impairment Score, NIS), neurophysiologic tests (m+7Ionis ), disability, and health scores were assessed in baseline evaluations of 100 patients entered into an oligonucleotide familial amyloidotic polyneuropathy (FAP) trial. Methods: We assessed: (1) Proficiency of grading neurologic signs and correlation with neurophysiologic tests, and (2) clinometric performance of modified NIS+7 neurophysiologic tests (mNIS+7Ionis ) and its subscores and correlation with disability and health scores. Results: The mNIS+7Ionis sensitively detected, characterized, and broadly scaled diverse polyneuropathy impairments. Polyneuropathy signs (NIS and subscores) correlated with neurophysiology tests, disability, and health scores. Smart Somatotopic Quantitative Sensation Testing of heat as pain 5 provided a needed measure of small fiber involvement not adequately assessed by other tests. Conclusions: Specially trained neurologists accurately assessed neuropathy signs as compared to referenced neurophysiologic tests. The score, mNIS+7Ionis, broadly detected, characterized, and scaled polyneuropathy abnormality in FAP, which correlated with disability and health scores. Muscle Nerve 56 : 901–911, 2017